O uso de simulações virtuais como apoio ao currículo da SEE-SP para a disciplina de Física - Rossi, Diego Delovo [UNESP] (2015)
This work supports a range of virtual experimental activities associated with the activities proposed by the curriculum of the Secretaria da Educação do Estado de São Paulo, which, besides contributing to the improvement of the teaching quality of this science, suggests a material to support the teacher who can subsidize a new methodological stance to their teaching practice. Virtual simulations and elaborate activities were selected compatible with various learning situations proposed by the curriculum of the São Paulo State Education to the discipline of physics, so that the end of the work all these activities were stored in a blog for teachers access showing interest in new alternatives for the development of their classes, still using the said curriculum. The methodology adopted for the development of simulated experimental activities was based on the significant learning Ausubel theory. The development of this work shows the teaching practice adopted and the activities developed aroused greater interest in students, as well as, collaborate with the execution of the established curriculum by the Secretaria da Educação. It is believed that, in addition to the proposed objectives, the development of this work contributed to the professional growth of educators and the intellectual development of students